From Freud to the present day: difference, not knowing and its relation to psychoanalysis. Issue 2 (3rd April 2019) - Jacobs, Amber
Abstract : In order to know and to understand we are often tempted to use defined models and theories. But catastrophe happens when you project models onto phenomena where they don't belong. Difference exists and not all phenomena can be forced to reside within existing models. We can project our already known theories and ideas onto what we think we see through certain frames that we create but the cost may be dear. There is no one way to understand the unconscious and the psyche. Psychoanalysis is always open for revision and development. Old models can be broken and new thought created. The unconscious is an impossible yet generative resource. We need to stay open to not knowing – constantly look at the frame and stay alert to its constructed nature. We need our frame to work with the unconscious but not to the detriment of the spirit of that unconscious.